Evaluating services for survivors of domestic violence and sexual assault - Riger, Stephanie (Sage series on violence against women., 2002)
Publisher's description: Evaluation programs that effectively measure the success of domestic violence and sexual assault services are essential not only to assure high levels of client service and continued funding, but also in evaluating how far society has come in the effort to end violence against women. Evaluating Services for Survivors of Domestic Violence and Sexual Assault provides comprehensive guidelines and field-tested tools for direct service evaluation programs. It also chronicles and celebrates over thirty years of progress made by the anti-violence movement. The authors offer a wealth of practical information at the same time identifying key issues and placing them in the broader context of social and political change. Essential reading for anyone who works in or is affiliated with programs serving the needs of victims of domestic violence and sexual assault, Evaluating Services for Survivors of Domestic Violence and Sexual Assault addresses the needs of both service providers and evaluators as well as funding agencies and policy makers.